Africa and the Olympic Movement: French Stakes, Strategies and Influences in the Internationalisation of African Sport (1944-1966) - (:unkn) unknown (My University, 2010)
Allocataire-moniteur puis ATER, rédaction de la thèse de septembre 2006 à novembre 2010.
Keywords: African Research